2022
DOI: 10.3390/tomography8050184
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced CT Texture Analysis in Colon Cancer: Correlation with Genetic Markers

Abstract: Background: The purpose of the study was to determine whether contrast-enhanced CT texture features relate to, and can predict, the presence of specific genetic mutations involved in CRC carcinogenesis. Materials and methods: This retrospective study analyzed the pre-operative CT in the venous phase of patients with CRC, who underwent testing for mutations in the KRAS, NRAS, BRAF, and MSI genes. Using a specific software based on CT images of each patient, for each slice including the tumor a region of interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In addition, contrast-enhanced CT is also used in CT texture analysis because of various blood supply characteristics of the tumor. [13][14][15] Previous studies also reported that 2-phase CT could differentiate neoplasms in salivary glands. [16][17][18] Therefore, this research was intended to evaluate the diagnostic ability of texture parameters by a 2-phase CT scan for the identification of SGTs (malignant and benign).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, contrast-enhanced CT is also used in CT texture analysis because of various blood supply characteristics of the tumor. [13][14][15] Previous studies also reported that 2-phase CT could differentiate neoplasms in salivary glands. [16][17][18] Therefore, this research was intended to evaluate the diagnostic ability of texture parameters by a 2-phase CT scan for the identification of SGTs (malignant and benign).…”
mentioning
confidence: 98%
“…Computed tomography texture analysis has been widely available in a variety of tumors and nononcologic applications, including head and neck cancer, 8 liver cancer, 9 lung cancer, 10 quantification of hepatic fibrosis, 11 and pulmonary fibrosis, 12 in predicting pathological features and assessment of therapy and prognosis. In addition, contrast-enhanced CT is also used in CT texture analysis because of various blood supply characteristics of the tumor 13–15 . Previous studies also reported that 2-phase CT could differentiate neoplasms in salivary glands 16–18 .…”
mentioning
confidence: 99%
“…The extraction of TA parameters from preoperative scans of patients with Stage III-IV CRC showed statistically significant differences in texture parameters between wild-type and mutated gene groups, indicating that CT TA can predict specific genetic mutations in CRC. This suggests a promising role for TA in noninvasive genetic assessments [ 22 ].…”
mentioning
confidence: 99%
“…12 Beyond that, CT texture features can provide information regarding the microstructure of tissues, which was shown in preliminary studies. [13][14][15][16][17][18][19] This is why texture features might also help to better characterize the content and different aspects of fluid collections to identify fungal associated changes, such as hyphae.…”
mentioning
confidence: 99%